2023
DOI: 10.3390/cancers15041217
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis Type 1: Pediatric Aspects and Review of Genotype–Phenotype Correlations

Abstract: Neurofibromatosis type 1 (NF1) is an autosomal dominant condition, with a birth incidence of approximately 1:2000–3000, caused by germline pathogenic variants in NF1, a tumor suppressor gene encoding neurofibromin, a negative regulator of the RAS/MAPK pathway. This explains why NF1 is included in the group of RASopathies and shares several clinical features with Noonan syndrome. Here, we describe the main clinical characteristics and complications associated with NF1, particularly those occurring in pediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 130 publications
0
12
0
Order By: Relevance
“…Peduto et al also demonstrated that large gene deletions correlate with a severe phenotype and that not all mutational variants have the same effects. Genotype-phenotype associations are on an upward curve at present, changing at a slower but profound pace the clinical and genetic approach to NF patients [3,24]. The splice site pathogenic variant identified in our patient has not been described in populational databases, so we cannot make an exact genotype-phenotype correlation.…”
Section: Genotype-phenotype Correlation In Nf1mentioning
confidence: 86%
See 1 more Smart Citation
“…Peduto et al also demonstrated that large gene deletions correlate with a severe phenotype and that not all mutational variants have the same effects. Genotype-phenotype associations are on an upward curve at present, changing at a slower but profound pace the clinical and genetic approach to NF patients [3,24]. The splice site pathogenic variant identified in our patient has not been described in populational databases, so we cannot make an exact genotype-phenotype correlation.…”
Section: Genotype-phenotype Correlation In Nf1mentioning
confidence: 86%
“…The prevalence of pathogenic variants in the NF1 gene is over 0.5% (31 different pathogenic variants), but the percentage of extremely rare or privately encountered variants is over 46% [22,23]. On the other hand, 90% of mutations occur in the intragenic region, with less than 10% being deletions that span the entire gene or are located in lacking genomic regions [24].…”
Section: Nf1 Genementioning
confidence: 99%
“…The prevalence of pathogenic variants in the NF1 gene is over 0.5% (31 different pathogenic variants), but the percentage of extremely rare or privately encountered variants is over 46% [20,21]. On the other hand, 90% of mutations occur in the intragenic region, with less than 10% being deletions that span the entire gene or are located in lacking genomic regions [22].…”
Section: Nf1 Genementioning
confidence: 99%
“…NF1 predominantly presents with benign tumors of the peripheral nervous system, called plexiform neurofibromas, as well as increased susceptibility to development of other brain and nerve tumors, including optic pathway gliomas and malignant peripheral nerve sheath tumors (MPNSTs) [14]. While typically considered an oncogenic predisposition syndrome, it is also associated with a number of non-tumor manifestations, including skeletal and skin pigmentation abnormalities (intense freckling, multiple Café-au-lait spots-CALSs), reduced overall growth, or short stature [14][15][16][17]. Neuronal impairments include executive and higher-order functions such as planning, visuospatial skills, reading/vocabulary, and motor coordination, sleep, learning, and cognitive impairments, including autism-like symptoms and attention deficits [18][19][20][21][22][23].…”
Section: Introduction 1neurofibromin and Neurofibromatosismentioning
confidence: 99%